Estrategias financieras para incrementar la rentabilidad de la empresa Supercomisariato San Rafael cantón Joya de los Sachas, provincia de Orellana - Villegas Ureña, Anderson Ramiro (2025)
The company Supercomisariato San Rafael, located in the canton of Joya de los Sachas, province of Orellana, faces a problem of low profitability due to the lack of adequate financial strategies and the acquisition of debts during the COVID-19 pandemic. This challenge has limited its capacity for growth and long-term sustainability. The main objective of this study is to determine the financial strategies that allow for improving the company's profitability, with a focus on identifying methods that enhance its financial viability. The main theories focus on the relationship between strategic financial planning and business sustainability, highlighting the relevance of long-term strategies that boost profitability and ensure continued success. The methodology applied is quantitative in approach, with a non-experimental design, and the research included interviews with the company's staff and a documentary analysis of its financial operations, which allowed a detailed evaluation of its financial weaknesses and strengths. The results showed that current strategies, focused on promotions and discounts, are insufficient and temporary, which has negatively affected the company's financial stability, increasing its vulnerability to unexpected crises. To solve this problem, it is concluded that developing a long-term financial strategy plan that includes a risk analysis and expansion into new markets is essential. This will improve profitability, reduce dependence on temporary strategies, and ensure the company's future sustainability. Your active involvement in this decision-making process is crucial for the company's success.